Evaluation of Dye Decolourization ability of Laccase Produced Curvularia lunata SS17 - Bello, A.; Hussaini, I. M. (UMYU Journal of Microbiology Research)
The increasing discharge of dyes into the environment and their consequential ecological effects has necessitated the need for the ecofriendly decolourization methods. Laccases became enzymes of research interest due to their broad substrates specificities. The aim of the study was to purify, characterize and determine the decolourization ability of Curvularia lunata SS17 produced laccase. Laccase was produced using maize cob as substrate under optimized culture conditions and purified using Gel Filtration Chromatography. Biuret method was then used to estimate the protein contents of the crude and partially purified laccase. Specific activities, purification fold and yield (%) of the crude and purified laccase enzyme were also estimated. Decolourization potentials of the crude and partially purified enzyme were evaluated using four dyes namely: Congo red, Methylene blue, Bromocresol green and direct yellow. Elution profile of partially purified laccase revealed that fraction 5 had the highest laccase activity (3.654 U/mL). Optimum conditions for enzyme activity were estimated to be 35oC and pH 6. Enzyme activity of the partially purified laccase (3.654 U/mL) was observed to be higher than that of the crude laccase (1.635 U/mL). Also, the partially purified laccase had higher specific activity (1.87 U/mg) compared to that of the crude laccase (0.41 U/mg). Higher percentage dye decolourization potential was observed using the partially purified laccase compared to the crude laccase. Increase in percentage decolourization of the dyes by the partially purified laccase as well as crude laccase was observed as incubation time proceeds.